Holocene desertification, traditional ecological knowledge, and human resilience in the eastern Gobi Desert, Mongolia. (December 2022) - Rosen, Arlene M; Janz, Lisa; Dashzeveg, Bukhchuluun; Odsuren, Davaakhuu
Dryland regions are particularly challenging for human survival over the course of deep time. This is true for institutionally complex communities as well as small-scale societies that have existed in semi-arid regions throughout the Holocene. This paper examines some of the successful strategies employed by small-scale mobile communities which enhanced their ability to thrive in drylands over the course of thousands of years. Small-scale societies living in drylands must rely on the transmission of Traditional Ecological Knowledge across generations. Some of this knowledge relates to the availability and use of wetlands and other more ephemeral water sources, the exploitation of a diverse range of resources, and the potential for natural storage of food resources as a buffer against regularly occurring drought years in these regions. We compare this understanding with our environmental archeological findings at the Mid-Holocene site of Zaraa Uul in the eastern Gobi Desert of Mongolia. At the site of Zaraa Uul, we show how hunter-gatherer groups returned to a campsite near the edge of a wetland environment over the course of at least two phases during the Mid-Holocene. Here they took advantage of a greater diversity of animal species and plants, including small-grained-grasses and sedges, which could enhance their caloric intake and increase the potential for storable commodities which could be collected as needed from their natural habitat.